Identification of a novel lncRNA prognostic signature and analysis of functional lncRNA AC115619.1 in hepatocellular carcinoma - Gan, Binliang; He, Youwu; Ma, Yonggang; Mao, Linfeng; Liao, Chuanjie; Deng, Ganlu (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC) is the deadliest malignancy. LncRNAs have involved in the development of multiple human malignances. This study aimed to establish a reliable signature and identify novel biomarkers for HCC patients. Methods: Differentially expressed lncRNAs (DElncRNAs) were identified from GEO and TCGA databases. Univariate, LASSO and multivariate Cox regression analyses were applied to screen the prognostic lncRNAs and establish prognostic model. ROC curves and Kaplan-Meier analyses were conducted to validate the prognostic value of this model. The association between lncRNAs and differential m6A genes were analyzed by spearman analysis. A series of bioinformatic and in vitro experiments were applied to explore the function of hub lncRNA. Results: A total of 32 DElncRNAs were identified and 12 DElncRNAs were associated to the prognosis of HCC patients. A prognostic signature comprising with six prognostic lncRNAs (LINC02428, LINC02163, AC008549.1, AC115619.1, CASC9 and LINC02362) were constructed and the model exhibited an excellent capacity for prognosis prediction. Furthermore, 12 differential m6A regulators were identified and RBMX was found to correlated negatively with hub lncRNA AC115619.1. The expression level of AC115619.1 was lower in HCC tissues than normal tissues and was significantly related to clinicopathology features, survival rate and drug sensitivity. Overexpression of AC115619.1 notably inhibited the proliferation, migration and invasion of HCC cells. Conclusion: This study provided a promising prognostic signature for HCC patients, and identified AC115619.1 as a novel biomarker which played an essential role in regulating progress of HCC.